Africa's Energy Renewal: The Twin Challenges of Energy Deficit and Climate Change. (21st October 2019) - Sy, Amadou N R; Simbanegavi, Witness; Ndung'u, Njuguna
Abstract: A significantly large energy deficit and high vulnerability to climate change seriously impede sub-Saharan Africa's path towards sustainable and inclusive growth. The extent to which the region can leverage the opportunities offered by renewable energy is an important policy question with implications for economic research. This special issue argues that policy and institutional reforms as well as good governance will play an important role in opening up the energy sector to private investment and expanding the fiscal space. Such a constellation, by increasing investment in the energy sector, would allow for increased access to reliable and affordable electricity by both households and businesses, which should help unleash Africa's potential. Several future areas of research are also identified.